The Role of Teachers in Islamic Religious Education: A Case Study of Vocational High School Students - Kasih, Fedly; Pasaleron, Roni; Nurfadhilah, Nurfadhilah; Efendi, Efendi (Al-kayyis: Journal of Islamic Education, 2025)
This study aims to describe the role of Islamic Education teachers in attracting students' interest in learning Islamic Education subjects in vocational high schools. This study was motivated by low student participation, a lack of variety in teaching methods, and minimal use of technology by teachers, which resulted in a monotonous and less conducive classroom atmosphere. The method used is qualitative with a case study approach, data collection techniques in the form of observation, interviews, and documentation. The main informants are Islamic Education teachers, with the principal and vice principal of curriculum as secondary data sources. The results show that the role of teachers in attracting students' interest in learning is still not optimal in three main aspects: personal interest, situational interest, and psychological interest. Teachers have not fully encouraged active student involvement, created enjoyable and relevant learning, and developed critical thinking skills. In addition, creativity in delivering material, effective interaction, and the use of technology still need to be improved. The implications of this study emphasize the importance of innovation in Islamic Religious Education learning strategies in order to be able to stimulate students' interest in learning in a comprehensive and sustainable manner.